2022
DOI: 10.3390/su142013160
|View full text |Cite
|
Sign up to set email alerts
|

Can Digital Inclusive Finance Promote Food Security? Evidence from China

Abstract: Eliminating hunger and ensuring food security is one of the specific goals of sustainable development of the United Nations in 2030, and food production is of great significance to food availability. Based on this, this paper investigates the impact of digital inclusive finance on food security by constructing a fixed effects model using panel data for 30 Chinese provinces from 2011 to 2020. The results found that: (1) Digital inclusive finance significantly and positively affects food security, and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…These findings fill the previously identified research gap by providing evidence that DIF can support agricultural operating income so as to enhance food security in China. Similar results were found in the studies by Lin et al (2022) and Gao et al (2022), wherein it was determined that digital inclusive finance can promote food security through the promotion of agricultural production in China [ 22 , 26 ]. Regarding disparities between agricultural functioning regions, the findings of this study are consistent with those obtained by Lin et al (2022).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings fill the previously identified research gap by providing evidence that DIF can support agricultural operating income so as to enhance food security in China. Similar results were found in the studies by Lin et al (2022) and Gao et al (2022), wherein it was determined that digital inclusive finance can promote food security through the promotion of agricultural production in China [ 22 , 26 ]. Regarding disparities between agricultural functioning regions, the findings of this study are consistent with those obtained by Lin et al (2022).…”
Section: Discussionsupporting
confidence: 85%
“…Due to its rapid development of digital inclusive finance, China has drawn the attention of academics who are interested in learning how this development may impact food security. Previous research has examined how digital inclusive finance affects the expansion of farmland and the upgradation of agricultural equipment [ 26 ] as well as the improvement of agricultural green total factor productivity [ 22 ]. Concerning the effect of digital inclusive finance on Chinese enterprises, previous studies have found that digital inclusive finance can relieve the financing constraints of small and medium-sized enterprises [ 18 , 19 , 20 ], help boost entrepreneurship [ 27 ], and promote innovation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the cost of risk identification, credit records and data acquisition for inclusive finance is high, and the general approach adopted by traditional inclusive finance is often difficult to balance the endogenous requirements of accessibility, affordability, comprehensiveness and commercial sustainability, so for inclusive finance to achieve long-term development, it also needs to find a new breakthrough, so the technology based on digital technology, mobile Internet, cloud computing, artificial intelligence, etc. Digital inclusive finance was born [68][69][70]. Technological progress is an important force to promote financial innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have confirmed the positive role of digital finance in improving work and production efficiency across industries, with deepening applications in various scenarios such as enterprise innovation, mass entrepreneurship, agricultural production and environmental governance. The conclusions showed that digital finance can significantly improve the quantity and quality of corporate green innovation, 52 promote household entrepreneurship 53 and food security production 54 and curb regional carbon emission intensity. 55 On the contrary, some scholars revealed that digital finance can widen the digital divide, negatively affecting entrepreneurial activities among residents in underdeveloped areas 56 and potentially hindering the initial digital transformation of agricultural enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%